Characteristics of Physicochemistry and Sensory of Arrowroot-wheat Flour Katte Tong with White Turmeric Powder and Carboxymethyl Cellulose Addition: Karakteristik Fisik, Kimia dan Kesukaan Katte Tong Pati Garut-terigu dengan Penambahan Bubuk Kunir Putih (Curcuma mangga Val.) dan Carboxymethyl Cellulose - Diannita, Estu Meylinda; Pujimulyani, Dwiyati; Murti, Siti Tamaroh Cahyono (Universitas Slamet Riyadi Surakarta, 2024)
Katte tong arrowroot-wheat flour has potential functional food that can be developed to optimize local ingredients. The addition of white saffron powder and CMC, which believed to provide health benefits because has high antioxidant activity and improve the texture to be sturdy. The purpose of this study was to determine the effect of the addition of white saffron powder and CMC on the physical, chemical and level of liking of katte tong arrowroot. This research was conducted to make katte tong with arrowroot-wheat flour with the addition of white saffron powder and CMC using a two-factorial completely randomized design (CRD). Factors included the addition of white saffron powder at 5, 10, 15% and CMC at 0.5, 1, 1.5%. Katte tong garut was then tested physically, chemically, and tested for favorability. The results showed that the addition of white saffron powder and CMC had a significant effect on the physical and chemical properties and preference level of the katte tong produced. The results of the analysis of the selected arrowroot katte tong have a moisture content of 1.82%bb, protein 7.89%bb, antioxidant activity of DPPH method 22.65% RSA, antioxidant activity of FRAP method 3.6 mg Efero/g and total phenols content 11.41 mg EAG/g.